Passion : Fan Behaviour and Art. - Tannert, Christoph; Künstlerhaus Bethanien, Berlin; Kunsthaus im KunstKulturQuartier, Nürnberg; Ludwig Múzeum Budapest; Stadtgalerie Kiel, Kiel; Barnitz, Miriam (Berlin : Künstlerhaus Bethanien GmbH, 2015)
Allen, Dave ; Bardolim, Juliana ; Voronzov, Sergey ; Barreto, Gilvan ; Beham, Eva ; Tröger, Sebastian ; Bell, Dirk ; Beyer, Klaus ; Breitz, Candice ; Bruce, Laura ; Bürner, Susanne ; Buttgereit, Jörg ; Butzmann, Frieder ; Cabello, Max ; Calovski, Yane ; Condo, George ; Czerepok, Hubert ; Dacorso, Daniela ; Dahn, Walter ; Deller, Jeremy ; Drühl, Sven ; Celinski, Lucas Foletto ; Garber, Pablo ; Gericke, Henryk ; Götze, Moritz ; massoud graf-hachempour ; Herbster, Julia ; Andy Hope 1930 ; Horvarth, Tibor ; IRWIN ; MK Kähne ; Killisch, Klaus ; Kirby, Cristian ; Kirsch, Helmut ; Kral, Christina ; Kroll, Jonathan ; Lazarus, Jason ; Lewandowsky, Via ; Lippok, Robert ; Lorent, Catherine ; Löser, Claus ; Motz, Jakobine ; Mandernach, Jörg ; Melgaard, Bjarne ; Mühlenbrock, Heiner ; Munch Andersen, Christoffer ; Mwaba, Stary ; Nemeth, Hajnal ; Pettibon, Raymond ; Peyton, Elizabeth ; Pousttchi, Bettina ; Richter, Daniel ; Rist, Pipilotti ; Rost, Andreas ; Rothschild, Miguel ; Sammlung Burmeister ; Sauter, Chris ; Schickert, Günter ; Schoemakers, René ; Schönfeld, Sarah ; Schulze, Hans J. ; Semu, Greg ; Shaw, Jeremy ; Simons, Raf ; Skadden, Elizabeth ; Süssmayr, Florian ; Szary, Sebastian ; Tanaami, Keiichi ; Tow, Nahuel ; Van de Moortel, Joris ; Vanetta, Fabrizia ; Vermeule, Koen ; Wahl, Lucas ; Weigand, Hans ; Wesely, Michael ; Wirthmann, Markus ; Witkowski, Adam ; Wong, Ming
Passion. Fan-Verhalten und Kunst / Fan Behaviour and Art, Künstlerhaus Bethanien, Berlin, 10.07.-09.08.2015 / Kunsthaus im KunstKulturQuartier, Nürnberg, 17.12.2015 - 14.02.2016 / Ludwig Muzeum, Budapest, 15.04. - 03.07.2016 / Stadtgalerie Kiel, Kiel, 10.09. - 13.11.2016
boek